2008
DOI: 10.1002/cl2.50
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Effectiveness of Programs to Prevent School Bullying

Abstract: School bullying is perceived to be an important social problem in many different countries. The nature and extent of the problem, and research on it, in 21 different countries, is reviewed in Smith et al. (1999). Special methods are needed to study bullying in different countries because of problems of translating the term "bullying" into different languages. Smith et al. (2002) have reviewed the meaning of bullying in 14 different countries. In studying bullying, researchers often ask about specific component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The review’s risk of bias (ROB) assessments and moderator analyses also deviated from plans described in the protocol [ 22 ] but these changes were not explained (as required by MECCIR R106). There were no plans for ROB assessment in the protocol (original plans for extraction of data on study qualities focused only on overall study designs and attrition).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The review’s risk of bias (ROB) assessments and moderator analyses also deviated from plans described in the protocol [ 22 ] but these changes were not explained (as required by MECCIR R106). There were no plans for ROB assessment in the protocol (original plans for extraction of data on study qualities focused only on overall study designs and attrition).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…There were no plans for ROB assessment in the protocol (original plans for extraction of data on study qualities focused only on overall study designs and attrition). Plans for moderator analysis were not specific, indicating that meta-regression would be used to “investigate independent influences of program components, methodological quality, features of participants, and design features” ([ 22 ] p. 12).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In addition, it appears that programs shifted in a positive direction teachers' knowledge of effective practices and efficacy of intervening and responding to incidences at school. Ttofi, Farrington, and Baldry (2008) simultaneously conducted a larger meta-analysis that included more studies. In a report for the Swedish National Council for Crime Prevention, they evaluated 44 bullying intervention studies.…”
Section: Meta-analytic Studies Of Bullying Prevention and Interventionmentioning
confidence: 99%
“…Teachers are the best people to implement these programs in their classrooms; however, they have many demands on their time and are likely to drift in their ability to adhere to bullying lesson implementation. Indeed, the recent meta-analyses (Ttofi et al, 2008) suggested that implementation level moderates the efficacy of school programs. That is, when programs are implemented with fidelity, then they are more likely to be effective than when the program is implemented in a piecemeal fashion.…”
Section: Meta-analytic Studies Of Bullying Prevention and Interventionmentioning
confidence: 99%